DESKRIPSI PEMBELAJARAN BIOLOGI DI KELAS VII SMPN 2 KUBUNG KABUPATEN SOLOK - Ferwati, Wita; Anhar, Azwir; F, Farida (Kolaboratif, 2014)
One of the problem faced in education is the ineffective learning process yet learning included lesson plan design, teaching and learning process and assessment done by teachers is not effective yet. The purpose of this research is to know the biology learning process in SMPN 2 Kubung Kabupaten Solok that covers planning, implementation and evaluation .Based on finding of the research, it is known that biology learning process in SMPN 2 Kubung Kabupaten Solok: (a) lesson plan designed by teacher in term of content the format of the leaning purpose was not arranged based on ABCD format. The teaching material and time allocation ware not elaborated completely; (b) teaching and learning process was seen from both teacher and students aspect. The teaching process done by teacher was not based on Permendiknas No. 41. year 2007, paedogogic and profesional competence did not implement well teaching skill was not good and the teacher less motivated the students; (c) the assessment done by the teacher was only in cognitive domain while affective and physycomotor were not done by teacher in all meetings.